Clinical Analysis of Chronic Active Epstein–Barr Virus Infection Involving the Gastrointestinal Tract. Issue 1 (11th October 2022) - Wei, Ang; Li, Zhigang; Ma, Honghao; Zhang, Liping; Zhang, Jing; He, Lejian; Lian, Hongyun; Zhang, Qing; Chen, Sitong; Xu, Jiatong; Wang, Dong; Liu, Wei; et al.
Abstract : Background: Chronic active Epstein‒Barr virus infection (CAEBV) is an intractable and progressive disease. T cells or NK cells infected by EBV can proliferate and infiltrate into multiple organs. CAEBV combined with gastrointestinal involvement is a rare clinical disease that has not been well described, and sometimes it may clinically mimic gastroenteritis or inflammatory bowel disease. Methods: This was an observational study that included all pediatric CAEBV patients who were treated at Beijing Children's Hospital, Capital Medical University, from June 2017 to June 2021. Patients were divided into the case group and the control group according to whether these patients had GI involvement. The children's clinical manifestations, laboratory and ultrasound examinations, treatment and prognosis were observed. Results: Seventy-two patients were enrolled in this study. Fifteen patients had GI involvement, including 11 males and 4 females, accounting for 20.8%, with a median onset age of 3.71 (0.64–14.47) years. The most common clinical manifestation at onset was diarrhea (13/15). Gastrointestinal ultrasound showed pneumatosis intestinalis, mild to moderate swelling of the surrounding mesentery and omentum and enhancement on ultrasound. The endoscopic features were hyperemia, edema and ulcers of variable morphological characteristics. Pathological examination showed lymphocyte infiltration with EBV-encoded small RNA (+), and the common locations of involvement were the colon (n = 6) and gastric antrum (n=3). The median follow-up time was 13.26 (0.31–51.89) months. Ten patients survived, and 5 patients died (including 1 who died of intestinal perforation because of necrotizing enterocolitis). Compared with the control group, the case group had higher alanine aminotransferase levels, aspartate aminotransferase and whole blood EBV-DNA copies ( P = 0.038, 0.040 and < 0.001) and lower natural killer cell activity ( P < 0.001). The 3-year overall survival rate of the case group was significantly lower than that of the control group (59.3% ± 12.9% vs. 79.4% ± 4.9%, P = 0.021). Conclusion: The incidence of CAEBV with GI involvement was low. The most common location of involvement was the colon. CAEBV with GI involvement had a poor prognosis. Patients with high whole blood EBV-DNA copy levels early in their illness were more likely to develop GI involvement.